1993
DOI: 10.1159/000182736
|View full text |Cite
|
Sign up to set email alerts
|

Course of Depression in Cushing’s Syndrome: Response to Treatment and Comparison with Graves’ Disease

Abstract: Depression is a common, life-threatening complication of Cushing’s syndrome and may occur in several other endocrine disorders. It is not clear, however, whether distinct features pertain to hypercortisohsm. We studied depression in Cushing’s syndrome differentiating pituitary-dependent and pituitary-independent forms, its incidence compared to Graves’ disease, and its appearance in the prodromal phase of both conditions. To 66 consecutive patients with Cushing’s syndrome and 70 with Graves’ disease, after tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
3

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 21 publications
8
56
1
3
Order By: Relevance
“…However, disappearance of psychiatric symptoms upon proper endocrine treatment is not always the case. In our experience and in previous investigations using definite diagnostic criteria for depression, about 70% of patients fully recovered from their depression after successful treatment of Cushing's syndrome, whereas there were no substantial changes in the others or even worsening in some (Sonino et al, 1993a). In those who actually deteriorated, the value of appropriate psychiatric intervention was underscored.…”
Section: Response To Treatmentsupporting
confidence: 46%
“…However, disappearance of psychiatric symptoms upon proper endocrine treatment is not always the case. In our experience and in previous investigations using definite diagnostic criteria for depression, about 70% of patients fully recovered from their depression after successful treatment of Cushing's syndrome, whereas there were no substantial changes in the others or even worsening in some (Sonino et al, 1993a). In those who actually deteriorated, the value of appropriate psychiatric intervention was underscored.…”
Section: Response To Treatmentsupporting
confidence: 46%
“…Its clinimetric features were assessed against those of Kellner’s [19]global scales of illness severity and changes after treatment (table 3). These scales are most commonly used for broad ‘global’ ratings [9], are often as sensitive or more sensitive than other criteria [19], and have been previously employed in patients with Cushing’s syndrome [20]. Their interrater agreement was assessed by ICC [16].…”
Section: Methodsmentioning
confidence: 99%
“…Although the common belief is that depression abates with the 'cure' of CD and the correction of hypercortisolism, few studies have prospectively examined the psychological profiles of patients with CD after correction of the hypercortisolemic state. In general, these studies reported that symptoms of depression decreased but were not eliminated after remission in some, but not all, patients (5,20,74,75,76).…”
Section: Comorbidities: Prevalence and Reversibilitymentioning
confidence: 98%